Effect of Non-invasive Vagus Nerve Stimulation on Resting-State Electroencephalography and Laser-Evoked Potentials in Migraine Patients: Mechanistic Insights - Vecchio, Eleonora; Bassez, Iege; Ricci, Katia; Tassorelli, Cristina; Liebler, Eric; de Tommaso, Marina (Frontiers in Human Neuroscience, 2018)
A recent multicenter trial provided Class I evidence that for patients with an episodic migraine, non-invasive vagus nerve stimulation significantly increases the probability of having mild pain or being pain-free 2 hours post stimulation. Here we aimed to investigate the potential effect of non-invasive vagus nerve stimulation in the modulation of spontaneous and pain related bioelectrical activity in a subgroup of migraine patients enrolled in the PRESTO trial by using resting-state electroencephalography and trigeminal laser-evoked potentials. Laser-evoked potentials were recorded for 27 migraine patients who received active or sham non-invasive vagus nerve stimulation over the cervical vagus nerve. We measured power values for frequencies between 2 and 100 Hz in a resting-state condition and the latency and amplitude of N1, N2, and P2 components of laser-evoked potentials in a basal condition during and after active or sham vagus nerve stimulation (T0, T1, T2). The P2 evoked by the right and the left trigeminal branch was smaller during active non-invasive vagus nerve stimulation. The sham device also attenuated the P2 amplitude evoked by the left trigeminal branch at T1 and T2, but this attenuation did not reach significance. No changes were observed for N1 amplitude, N1, N2, P2 latency, or pain rating. Non-invasive vagus nerve stimulation induced an increase of EEG power in both slow and fast rhythms, but. this effect was not significant as compared to the sham device. These findings suggest that non-invasive vagus nerve stimulation acts on the cortical areas that are responsible for trigeminal pain control and pave the ground for future studies aimed at confirming the possible correlations with clinical outcomes, including the effect on symptoms that are directly correlated with trigeminal pain processing and modulation.